Large trisoctahedral Au nanoparticles encapsulated inside porous silica catalyses CO oxidation at room temperature: probing the effect of encapsulation and the role of step atoms and interfaces - Sreedhala, S.; Maheshwari, Shruti; Betsy, K. J.; Vinod, C. P. (Applied Catalysis A-General, 2016)
As envisaged, a synthesis strategy is reported for encapsulating high index faceted trisoctahedral Au nanoparticles inside porous silica to preserve nanoparticle size by preventing sintering. Further, to probe the role of interfaces an active metal oxide junction was created by decorating trisoctahedral (TOH) Au nanoparticle with nano oxides before silica encapsulation. The activity of these catalysts was tested for CO oxidation reaction. The reaction was found to be facile on these encapsulated large structured Au nanoparticles showing appreciable activity at room temperature compared to non encapsulated counterparts. Apart from preventing sintering, the improved activity is demonstrated due to the retention of morphology and thereby the active centres due to encapsulation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Defect sites; Encapsulation; High index facets; Metal-oxide active perimeter; Trisoctahedral Au nanoparticles